2021
DOI: 10.3389/fonc.2021.774156
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Unique Clinical and Genetic Features of Chinese Lung Cancer Patients With EGFR Germline Mutations in a Large-Scale Retrospective Study

Abstract: BackgroundEpidemiological surveys have suggested that lung cancer has inherited susceptibility and shows familial aggregation. However, the distribution and prevalence of epidermal growth factor receptor (EGFR) germline variants and their roles in lung cancer genetic predisposition in Chinese population remain to be elucidated.MethodsIn this study, EGFR germline and somatic variants were retrospectively reviewed from the next-generation sequencing results of 31,906 patients with lung cancer. Clinical informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The same mutations were found in five paternal relatives of the patient, and three of them were also found to have multiple GGNs. Furthermore, a recent study enrolled 162 probands with MPLC showing an EGFR germline mutation rate as high as 9.8%, 112 which is far higher than the rate of 0.01% in the general population, 113 and approximately 0.2% in the entire set of lung cancer patients 114 . The rate of germline mutations in lung cancer varies between 0.2% and 7.0%, depending on the inclusion criteria and study settings, 115–123 and a recent study reports a rate reaching 15% in over 7000 unselected lung cancer, with 95% being clinically actionable 124 .…”
Section: Etiology Evolutionary Trajectory Of Mplc and Clinical Implic...mentioning
confidence: 99%
See 1 more Smart Citation
“…The same mutations were found in five paternal relatives of the patient, and three of them were also found to have multiple GGNs. Furthermore, a recent study enrolled 162 probands with MPLC showing an EGFR germline mutation rate as high as 9.8%, 112 which is far higher than the rate of 0.01% in the general population, 113 and approximately 0.2% in the entire set of lung cancer patients 114 . The rate of germline mutations in lung cancer varies between 0.2% and 7.0%, depending on the inclusion criteria and study settings, 115–123 and a recent study reports a rate reaching 15% in over 7000 unselected lung cancer, with 95% being clinically actionable 124 .…”
Section: Etiology Evolutionary Trajectory Of Mplc and Clinical Implic...mentioning
confidence: 99%
“…111 The same mutations were found in five paternal relatives of the patient, and three of them mutation rate as high as 9.8%, 112 which is far higher than the rate of 0.01% in the general population, 113 and approximately 0.2% in the entire set of lung cancer patients. 114 The rate of germline mutations in lung cancer varies between 0.2% and 7.0%, depending on the inclusion criteria and study settings, [115][116][117][118][119][120][121][122][123] and a recent study reports a rate reaching 15% in over 7000 unselected lung cancer, with 95% being clinically actionable. 124 Since individuals with MPLC appear to be more susceptible to germline mutations, along with the potential for high germline mutation rates in lung cancer, a potentially sizable MPLC population harboring targetable germline mutations should be anticipated, and targeting germline mutation may serve as a new therapeutic approach for MPLC in the future.…”
Section: Etiologymentioning
confidence: 99%
“…Germline mutations of EGFR, V‐erb‐b2 avian erythroblastic leukemia viral oncogene homolog 2 (ERBB2), checkpoint kinase 2 (CHEK2), and cyclin‐dependent kinase inhibitor 2A were detected in lung cancer patients [ 74 , 75 , 76 ]. In a large‐scale study of 31,926 Chinese lung cancer patients, 22 types of EGFR germline mutations were identified in 64 lung cancer individuals (0.2%), among which G863D was the most frequent type of mutation (14.1%, 9/64) [ 75 ]. In 12,833 Chinese lung cancer cases, 0.12% harbored EGFR germline mutation ( n = 14) [ 76 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…The morbidity of the P848L population is currently unclear. A large-scale retrospective study involving 31,906 Chinese patients with lung cancer found 22 germline EGFR variants in 64 patients with lung cancer, while germline EGFR P848L account for 10.9% (7/64) of the patients with EGFR germline mutation (29). A further study of 120 patients with colorectal or lung cancer reported that only one patient exhibited the P848L mutation (30).…”
Section: Germline Mutation Of Egfr P848lmentioning
confidence: 99%